2011
DOI: 10.5194/acp-11-12369-2011
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol hygroscopicity and CCN activation kinetics in a boreal forest environment during the 2007 EUCAARI campaign

Abstract: Abstract. Measurements of size-resolved cloud condensation nuclei (CCN) concentrations, subsaturated hygroscopic growth, size distribution, and chemical composition were collected from March through May, 2007, in the remote Boreal forests of Hyytiälä, Finland, as part of the European Integrated project on Aerosol Cloud Climate and Air Quality Interactions (EUCAARI) campaign. Hygroscopicity parameter, κ, distributions were derived independently from Continuous Flow-Streamwise Thermal Gradient CCN Chamber (CFSTG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
119
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(143 citation statements)
references
References 89 publications
23
119
1
Order By: Relevance
“…A peak in aerosol hygroscopicity is observed around midday when D c reaches its minimum. Several previous studies have reported such behaviour in Hyytiälä and have attributed it to the vegetation activity, photochemistry and the ageing of organics during sunlight hours (Sihto et al, 2011;Cerully et al, 2011;Paramonov et al, 2013). While no diurnal pattern of aerosol hygroscopicity is visible for Jungfraujoch for winter and spring, a very clear pattern does exist in the summer and autumn.…”
Section: Ccn and Their Hygroscopicitymentioning
confidence: 83%
“…A peak in aerosol hygroscopicity is observed around midday when D c reaches its minimum. Several previous studies have reported such behaviour in Hyytiälä and have attributed it to the vegetation activity, photochemistry and the ageing of organics during sunlight hours (Sihto et al, 2011;Cerully et al, 2011;Paramonov et al, 2013). While no diurnal pattern of aerosol hygroscopicity is visible for Jungfraujoch for winter and spring, a very clear pattern does exist in the summer and autumn.…”
Section: Ccn and Their Hygroscopicitymentioning
confidence: 83%
“…Heterogeneity in the chemical composition and particle size both contribute to broadening of p(s c ) (Lance, 2007;Svenningsson and Bilde, 2008;Rose et al, 2008;Cerully et al, 2011) and affects the slope parameter, C, of the activation spectrum.…”
Section: Ccn Measurements and Derivation Of κ Ccncmentioning
confidence: 99%
“…To obtain size-resolved CCN activation spectra, a similar experimental setup to Cerully et al (2011) was used. The sampled aerosol was electrostatically classified with a differential mobility analyzer (nanoDMA, TSI 3085) (Chen et al, 1998) using a 210-Po neutralizer.…”
Section: Measurements and Instrumentationmentioning
confidence: 99%
“…To account for hygroscopicity and dry size differences between aerosol, both droplet sizes are selected from the point where activation is first observed. TDGA has been applied to several ambient aerosol samples (AsaAwuku et al, 2011;Bougiatioti et al, 2009Bougiatioti et al, , 2011Lance et al, 2009;Murphy et al, 2009;Padró et al, 2010Padró et al, , 2011Cerully et al, 2011), secondary organic aerosol (SOA) (Engelhart et al, 2008(Engelhart et al, , 2011Asa-Awuku et al, 2009 and laboratory-generated aerosol (Moore et al, 2008;Kumar et al, 2011a,b). In general, slower kinetics than calibration aerosol have been related to insoluble organics from SOA chamber experiments (Asa-Awuku et al, 2009), fresh exhaust plumes , and mineral dust particles when using a dry generation technique (Kumar et al, 2011a,b).…”
Section: T Raatikainen Et Al: Activation Kinetics From Measurementsmentioning
confidence: 99%